Analisis Penerapan Loyalty Program pada Industri Perhotelan di Surabaya - Susanti, Christina Esti (Kajian Manajemen dan Bisnis, 2010)
Loyalty program, as a type of relationship marketing, consists of economic, social, and structural benefits. The benefits can make consumers loyal. The consumer's loyalty increases corporate profitability. The goal of this research is to know the the influence of loyalty program toward consumer's loyalty particularly in the hotel industry in Surabaya. The type of the research used is a causality survey. The result shows that there is a significant influence of loyalty program toward consumer's loyalty in the hotel industry in Surabaya.